Yemi's Big Match - Milsome, John (Evans Brothers Ltd, 1982)
In this story set in Africa, football-mad Yemi is heart-broken when his school closes with the subsequent loss of the football pitch. A special football match is arranged with Nigeria's star team to collect money for a school with equal sports facilities, but the plans are forestalled by some unexpected events...
Keywords: Juvenile Fiction